Acidentes com material biológico entre trabalhadores da área da saúde da região metropolitana de Goiânia-GO: uma análise de 25 anos de registros - Neves, Zilah Cândida Pereira das (2016)
Accidents with biological material are reportable events, health care workers (TAS), victims of these accidents may be exposed to the hepatitis B and C and HIV, among others. The aims of this study were: to analyze the epidemiology of occupational accidents with biological material among health care workers of the metropolitan area of Goiania-GO (general); describe the socio-demographic and occupational profile of health care workers, victims of occupational accidents with biological material; describe the profile of accidents with biological material among health care workers; characterize the adoption of pre-exposure behaviours related to the latest accident; identify the serological status related to hepatitis B, C and HIV in victims of occupational accidents involving biological material and source patients, and establish the demographic and employment factors associated with the occurrence of multiple accidents among health care workers of the metropolitan area of Goiania-GO. Epidemiological Cross and analytical study which included all registration records of accidents involving biological material of HCW from two sources: A - records of injured HCW in a reference hospital for notification in Goiania, from the first record in 1989 to 2010, and B - records of Sinan, including the first record in 2006 until those available at 31/12/2014. Linkage of databases was performed and data analyzed using the Statistical Package for Social Sciences (SPSS). Socio-demographic and employment variables were the predictor variables and have suffered more than one accident, the outcome. Univariate analysis was performed and variables with P<0.10 were included in a logistic regression model. Ethical precepts were followed (Approval Ethics Committees: 033/2010 and 414.258/2013). A total of 11,536 accidents were recorded from 1989 to December 2014. Of these, 9,575 (83.0%) occurred among HCW and the majority was female. It was found that 665 (7.5%) of the HCW experienced more than one accident, while 70 (0.8%) experienced three or more accidents, totaling 8,825 victims. Nursing staff, auxiliary cleaning, physician, and dental and laboratory teams were the ones who were more frequently hurted, respectively. Most of the victims had completed high school (3,719 (48.0%). Blood/serum/plasma were the biological materials found to be the most involved (6,480/67.7%), at the time of administering medications/vascular access puncture occurring in 2.759 (28.9%), and involving needles with and without lumen in 6,097 (63.7%). A total of 6,653 (75.4%) HCW were vaccinated for hepatitis B. Incomplete information on Sinan records such as, use of PPE (gloves, masks, boots and safety glasses) and serological markers (HBsAg; Anti-HBs, Anti-HCV and Anti-HIV) was found to be the major factor that hampered data analysis. Age, type of material, and organic fluid were predictors risk factor for multiple accidents involving biological material among health care workers.